Vitamin K Vitamers Differently Affect Energy Metabolism in IPEC-J2 Cells - Bernardini, Chiara; Algieri, Cristina; La Mantia, Debora; Trombetti, Fabiana; Pagliarani, Alessandra; Forni, Monica; Nesci, Salvatore (Frontiers in Molecular Biosciences, 2021)
The fat-soluble vitamin K (VK) is long known to be required for blood coagulation, but like other vitamins, has been recently recognized to play further physiological roles, particularly in cell development and homeostasis. Vertebrates cannot de novo synthesize VK, which is essential and can only be obtained from the diet or by the activity of the gut microbiota. The IPEC-J2 cell line, obtained from porcine small intestine, which shows strong similarities to human one, represents an excellent functional model to in vitro study the effect of compounds at the intestinal level. The acute VK treatments on the bioenergetic features of IPEC-J2 cells were evaluated by Seahorse XP Agilent technology. VK exists in different structurally related forms (vitamers), all featured by a naftoquinone mojety, but with distinct effects on IPEC-J2 energy metabolism. The VK1, which has a long hydrocarbon chain, at both concentrations (5 and 10 µM), increases the cellular ATP production due to oxidative phosphorylation (OXPHOS) by 5% and by 30% that by glycolysis. The VK2 at 5 μM only stimulates ATP production by OXPHOS. Conversely, 10 μM VK3, which lacks the long side chain, inhibits by 30% OXPHOS and by 45% glycolysis. However, even if IPEC-J2 cells mainly prefer OXPHOS to glycolysis to produce ATP, the OXPHOS/glycolysis ratio significantly decreases in VK1-treated cells, is unaffected by VK2 and only significantly increased by 10 μM VK3. VK1, at the two concentrations tested, does not affect the mitochondrial bioenergetic parameters, while 5 μM VK2 increases and 5 μM VK3 reduces the mitochondrial respiration (i.e. maximal respiration and spare respiratory capacity). Moreover, 10 μM VK3 impairs OXPHOS, as shown by the increase in the proton leak, namely the proton backwards entry to the matrix space, thus pointing out mitochondrial toxicity. Furthermore, in the presence of both VK1 and VK2 concentrations tested the glycolytic parameters, namely the glycolytic capacity and the glycolytic reserve, are unaltered. In contrast, the inhibition of glycoATP production by VK3 is linked to the 80% inhibition of glycolysis, by resulting in a reduced glycolytic capacity and reserve.